Scaling early child development: what are the barriers and enablers?. (12th April 2019) - Cavallera, Vanessa; Tomlinson, Mark; Radner, James; Coetzee, Bronwynè; Daelmans, Bernadette; Hughes, Rob; Pérez-Escamilla, Rafael; Silver, Karlee L; Dua, Tarun
Abstract : The Sustainable Development Goals, Global Strategy for Women's, Children's and Adolescents' Health (2016–2030) and Nurturing Care Framework all include targets to ensure children thrive . However, many projects to support early childhood development (ECD) do not 'scale well' and leave large numbers of children unreached. This paper is the fifth in a series examining effective scaling of ECD programmes. This qualitative study explored experiences of scaling-up among purposively recruited implementers of ECD projects in low- and middle-income countries. Participants were sampled, by means of snowball sampling, from existing networks notably through Saving Brains®, Grand Challenges Canada®. Findings of a recent literature review on scaling-up frameworks, by the WHO, informed the development of a semistructured interview schedule. All interviews were conducted in English, via Skype, audio recorded and transcribed verbatim. Interviews were analysed using framework analysis. Framework analysis identified six major themes based on a standard programme cycle: planning and strategic choices, project design, human resources, financing and resource mobilisation, monitoring and evaluation, and leadership and partnerships. Key informants also identified an overarching theme regarding what scaling-up means. Stakeholders have not found existing literature and available frameworks helpful in guiding them to successful scale-up. Our research suggests that rather than proposing yet more theoretical guidelines or frameworks, it would be better to support stakeholders in developing organisational leadership capacity and partnership strategies to enable them to effectively apply a practical programme cycle or systematic process in their own contexts.